A-158 Levels of Systemic Inflammation is Associated with Cognitive Function in People with Multiple Sclerosis. (17th August 2022) - Collette, Christopher W; Norling, Amani M; Ward, Katherine; Freeman, Hyun; Myers, Terina; Bashir, Khurram; Lazar, Ronald M; Gerstenecker, Adam
Abstract: Objective: To investigate the relationship between systematic inflammatory biomarkers and cognition in patients with Multiple Sclerosis (MS). Method: We recruited 36 patients diagnosed with MS (31 with relapsing-remitting and 5 with progressive) who presented for treatment at the University of Alabama at Birmingham (UAB). Patients underwent a comprehensive neuropsychological battery, and serum blood samples were collected. Cognitive data was divided into an overall Cognitive Composite score and seven cognitive domains (i.e., Attention, Verbal Memory, Visual Memory, Visuospatial Ability, Language, Processing Speed, and Executive Function) using z-score averages. Pearson's product-moment correlations were conducted to determine the relationship between cognitive performance and 14 inflammatory biomarkers specifically chosen for their potential role in MS. Results: Matrix Metalloproteinase-9 (MMP-9) was significantly correlated with Visual Memory (r= -.424; p=.01), Language (r= -.425; p= .01), and Cognitive Composite (r= -.380; p= .022) scores. Additionally, Insulin-like Growth Factor-1 (IGF-1) was significantly correlated with the overall Cognitive Composite (r= -.346; p= .039) score. Conclusions: Studies investigating associations between inflammation and cognition in MS are lacking. In our sample of persons with Multiple Sclerosis, serum IGF-1 and MMP-9 biomarkers were moderately negatively correlated with the overall Cognitive Composite scores. MMP-9 was negatively correlated with Visual Memory and Language cognitive domain scores. These findings in a representative sample of patients with MS highlight the need for further research exploring the relationship between systematic inflammatory biomarkers and cognition in MS.